FISH CATCHING TRIALS WITH TWO DIFFERENT TYPES OF FISH POTS IN KEBAN DAM LAKE (TURKEY-ELAZIG) - Atessahin, Tuncay; Duman, Erdal (Parlar Scientific Publications (P S P), 2018)
Two different fish pot models were used in two catching areas with no bait (controls) and barley bait at three different depths (5-10, 11-15 and 16-20 m) during the period July 2013 and March 2014. In the study, 18 trials were completed; of the 1,474 fishery products caught, 109 (7.4%) were crayfish, and 1,365 (92.6%) comprised other fish species. The highest number of fish caught belonged to the Acanthobrama marmid genus (1,084 [73.7%]), followed by Cyprinus carpio (95 [6.4%]), Alburnus mossulensis (67 [4.6%]) and Luciobarbus esocinus (62 [4.6%]). Of the total 139.931 kg fish weight, 87.434 (62.48 %) kg and 52.497 (37.52 %) kg were caught with A and B model fish pots, respectively. During the study period, of the total 1,474 individuals caught, 694 (47.1 %) were caught using barley bait, and 780 (52.9 %) constituted the control group. Of the total catch of 139.931 kg fish, 66.6% (93.209 kg) were caught in the fish pots with barley bait, and 33.4 % (46.721 kg) were caught in the control fish pots. The average length of the fish caught with both fish pot models were found to be similar, although there were some slight differences. The average sizes of C. carpio, A. marmid, O. mykiss and A. leptodactylus were similar for both fish pots; however, L. esocinus, L. mysteceus, M, mastecembelus, A. mossulensis, C. umbla and B. grypus favoured the A model, and others favoured the B model. For the A model fish pots, the minimum catch per unit effort (CPUE) value (30.33 g) was observed in January, and the maximum value (118.65 g) was noted in March 2014. For the B model fish pots, the minimum CPUE value (14.06 g) was observed in October 2014, and the maximum value (72.69 g) was noted in November 2014. The average CPUE value per trial was calculated at 67.64 g for the A model fish pots and 39.41 g for the B model fish pots. The average CPUE monthly values of both fish pot models were found to be different (p < 0.05).
Keywords: Keban Dam Lake; Model of Fish Pots; Bait; Catch Efficiency